(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Perforation peritonitis is one of the most prevalent and challenging surgical emergencies in India, often leading to significant postoperative complications. One such complication, as a way to stimulate gastrointestinal motility and potentially reduce the duration of postoperative ileus (POI), is characterized by a delayed return of bowel function. POI leads to prolonged recovery times, increased healthcare costs, and patient discomfort. Gum chewing, a simple and inexpensive method of "sham feeding," has been suggested in reducing POI following surgery. Objective: To determine the effectiveness of gum chewing (non-sugared) in reducing post operative ileus in cases of perforation peritonitis undergoing primary closure. Material and methods: This study was conducted prospectively in the Department of General Surgery, Government Medical College & Rajindra Hospital, Patiala. Data for this prospective study was sourced from postoperative patients who underwent surgery for perforation peritonitis with primary closure at Government Medical College & Rajindra Hospital, Patiala, during the period of study from 1st August 2023 to 31 July 2024. Total 60 cases were enrolled. Group A (n=30) received non-sugared gum to chew thrice daily after recovery from anaesthesia until passage of first flatus. Group B (n=30) received standard postoperative care. Outcomes accessed included appearance of bowel sounds, time to first flatus, defecation time, time to acceptance of first enteral liquid diet, and duration of hospital stay. Results: Bowel sounds returned earlier (37.43 ± 8.43 vs. 58.76 ± 9.43 hours, p < 0.0001), Mean time to first flatus was 47.43 ± 7.36 hours in Group A versus 61.53 ± 6.96 hours in Group B (p < 0.0001)., and defecation occurred sooner (90.87 ± 3.42 vs. 110.30 ± 22.17 hours, p < 0.0001). Patients in Group A tolerated enteral liquid diet earlier and had a significantly shorter hospital stay (8.83 ± 2.03 vs. 11.30 ± 1.51 days, p < 0.0001). The mean age in group A was 42.87±7.36 years (range 19-75) and mean age in group B was 41.13±16.80 years (range 20- 80). Conclusion: While both groups had similar age and gender distributions, postoperative patients who were given chewing gum (non- sugared) demonstrated a faster recovery trajectory across several key indicators, including time to pass flatus, defecation, resumption of normal dietary intake and had less hospital stay. Additionally, postoperative patients on chewing gum (non- sugared) experienced a shorter hospital stay and an earlier return of bowel function. Suggesting that the approach used in chewing gum group may be more effective in promoting quicker recovery following surgery, highlighting its potential benefits for patient management in similar clinical settings.